A device to study the simultaneous heat and moisture movement in soils. Issue 5 (8th August 2014) - Rao, Bendadi Hanumantha
Abstract : Studies of simultaneous heat and moisture movement in soils are essential to characterise the thermal stability of the medium and to understand the soil water dynamics in the vadose zone. Although, many laboratory, analytical and mathematical models have been developed, small-scale laboratory tests found to be quite useful in understanding the behaviour of model materials and evaluating the influence of various interrelated parameters on heat and moisture movement in the soil mass. This paper presents the usefulness of a simple device (i.e. a thermal probe) that can be employed to study the simultaneous heat and moisture movement in kaolin. The device, which was fabricated in-house, is easy to use, handy and cost effective. It imposes a line-heat source of thermal flux in the soil mass that creates a thermal gradient causing moisture movement to take place from higher to lower temperature regions. It has been noticed that the device is very efficient and quite useful to carry out experiments related to simultaneous heat and moisture movement in soils. Further, attempts were also made to demonstrate the distinct advantage of electrical properties to measure the instantaneous moisture content of kaolin in a non-destructive and non-invasive manner.